(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2012)
Biological and psychosocial factors along with cumulative environmental factor have effect on the later childhood development. The detrimental effect of these factors on development varies from studies to studies in different geographical regions with variation in the causality. LBW (Low birth weight) children (birth weight<2500 g) generally have poorer levels of development compared to NBW (Normal birth weight) infants. The development of term-LBW/SGA (Small for gestanational age) or IUGR (Intrauterine growth retardation) infant is more complex and controversial. To assess the factors influencing cognitive development of Bangladeshi infants from poor socio-economic background. This study was conducted using pooled data derived from a previously done randomized control trial on 400 pregnant women. To find the biological and socio-environmental factors that associated with development, we broke down the randomization. A house-to-house survey was carried out in a defined poor urban area and all women who were 5 to 6 months pregnant were enrolled and the gestational period was ascertained by the report of LMP (Last menstrual period) given by the mothers. Data of 249 mother-infant dyads who completed the study and had all the measurements up to 10 months were used for this analysis. The detailed information regarding enrolment and findings from the main study has been published elsewhere. Distribution of each variable was checked for normality and where necessary appropriate transformations were made. Bivariate correlations between the developmental variables and socioeconomic measures were assessed. To examine the effect of biological and psychosocial factors on development of infants, series of multiple linear regression analyses were performed where each of the developmental variables was treated as a dependent variable. Family wealth and play material available for the child at home have a strong positive influence on both mental and psychomotor development whereas overcrowding exerts a negative impact on development. Similarly younger infants, being female, having larger head at birth and greater increase in head size over 10 month were found to have better mental developmental index, while taller children at birth had better psychomotor development at 10 month. Birth length and head-circumference and growth in head-circumference in the early months affect child development even after controlling for social background. JCMCTA 2012; 23(1): 11-16